Evaluasi Kualitas Kesehatan Hunian di Permukiman Pesisir Sendang Biru, Kecamatan Sumbermanjing Wetan, Kabupaten Malang - Israjab, Reksa; Hidayat, Taufik (Anoa : Jurnal Pengabdian Masyarakat Fakultas Teknik, 2024)
A settlement is a residential environment where humans live and carry out activities that support their livelihoods. A house is a part of the place where people live. A house with healthy physical conditions is an indicator of the achievement of community welfare. The settlement is located in the coastal area of Tambakrejo Village, Sumbermanjing Wetan District, Malang Regency. This study aims to analyze the health level of residents' houses using qualitative methods through observation and interviews. Healthy criteria in the arrangement of space utilization for personal and communal spaces are based on the Healthy House Principles set by the Ministry of Public Works and Housing (PUPR). The results show that the houses in the Coastal Settlement of Sendang Biru are categorized as healthy, in accordance with PUPR regulations.